2011
DOI: 10.3168/jds.2010-3684
|View full text |Cite
|
Sign up to set email alerts
|

Effect of type traits on functional longevity of Czech Holstein cows estimated from a Cox proportional hazards model

Abstract: Relationships between conformation traits and functional longevity in Holstein cows were evaluated using survival analysis. Functional longevity was defined as the number of days between the first calving and culling; that is, length of productive life. The data set consisted of 116,369 Holstein cows that first calved from 2003 to 2008. All cows used in the analysis were scored for conformation between d 30 and d 210 of their first lactation. The data included 48% censored records. Analyses were done separatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
3
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(92 citation statements)
references
References 17 publications
7
73
3
9
Order By: Relevance
“…Dadpasand et al (2008) observed a slightly different order for the risk of culling, which ranged between 0.78 and 1.73 for fore udder attachment, 0.89 and 1.64 for udder depth, 0.98 and 1.26 for fore teat placement and 0.75 and 1.07 for suspensory ligament, against a reference score class of 5 within the score range of 1 to 9. Udder depth has been reported to have the highest relative contribution to survival likelihood, and therefore had the highest effect on cow survival after correction for milk production (Bünger & Swalve, 1999;Caraviello et al, 2003;Zavadilová et al, 2011). Dadpasand et al (2008), Sewalem et al (2005a) and Caraviello et al (2003;2004b) reported an intermediate optimum for udder depth, implying that cows with very deep or very shallow udders were at high risk of being culled from the herds.…”
Section: Type and Udder Traitsmentioning
confidence: 99%
See 4 more Smart Citations
“…Dadpasand et al (2008) observed a slightly different order for the risk of culling, which ranged between 0.78 and 1.73 for fore udder attachment, 0.89 and 1.64 for udder depth, 0.98 and 1.26 for fore teat placement and 0.75 and 1.07 for suspensory ligament, against a reference score class of 5 within the score range of 1 to 9. Udder depth has been reported to have the highest relative contribution to survival likelihood, and therefore had the highest effect on cow survival after correction for milk production (Bünger & Swalve, 1999;Caraviello et al, 2003;Zavadilová et al, 2011). Dadpasand et al (2008), Sewalem et al (2005a) and Caraviello et al (2003;2004b) reported an intermediate optimum for udder depth, implying that cows with very deep or very shallow udders were at high risk of being culled from the herds.…”
Section: Type and Udder Traitsmentioning
confidence: 99%
“…The relative contribution of udder-type traits to risk of culling and hence likelihood of survival has been well documented (e.g. Bünger et al, 2001;Dadpasand et al, 2008;Zavadilová et al, 2011). Some researchers have listed udder traits as having a significant impact on longevity.…”
Section: Type and Udder Traitsmentioning
confidence: 99%
See 3 more Smart Citations